Sinthesis and effectiveness analysis of the invariant algorithms of turbulent zone signal processing for weather radar - Прокопенко, И. Г.; Яновский, Ф. И.; Лигхарт, Л. П.; Прокопенко, К. И. (Proceedings of National Aviation University (archive), 1999)
On the basis of Markov model of radar signals reflected from hydrometeorological formations, the synthesis of new invariant (relatively to noise power) algorithms for turbulent zone detection is made. Comparative analysis of synthesized and known algorithms is carried out by the method of statistical simulation